Further Studies on Species of Deladenus Thorne, 1941 from Haryana, India (Indian Journal of Nematology, 2024)
Six species of Deladenus, four collected from the bark of insect borer-infested trees and two from the rhizosphere of crops plants from Haryana are described. Deladenus pinusus n. sp.: Mycophagous female: L= 0.76-1.16 mm, a= 22-40, b= 9.6-14.9, b’= 4.3-6.6, c= 17.3-30.1, V= 89.4-93.4, c’= 1.9-4.2, stylet = 9-10 μm, tail = 23-42 μm. Lateral lines 8-9. Excretory duct cuticularized. Hemizonid 27-39 μm behind excretory pore. Spermatheca rounded, sperms rounded without distinct nuclei. Post vulval uterine sac absent. Tail elongated conoid, tapering from both sides to a broadly pointed to mucronate terminus. Mycophagous male: L= 0.63- 0.83 mm, a= 28-42, b= 7.2-9.3, b’= 3.6-5.1, c= 17.1-25.9, c’= 1.7-3.8, stylet = 9-10 μm, tail = 26-39 μm, spicules= 15-19 μm. Spermatozoa of two types but only one type in a single individual. Infective female: L= 1.10-1.70 mm, a=59-102, b= 8.9-12.2, b’= 2.4-3.4, c= 14.8- 21.4, V= 88.5-90.7, c’= 6.2-8.1, stylet = 10-12 μm, tail = 65-106 μm. Body very thin. Shaft of stylet 7-9 μm long with wide lumen and well developed basal swellings. Post vulval uterine sac absent. Tail elongated conoid, tapering from both the sides and ending in a narrowly pointed to mucronate terminus. Deladenus uteropinusus n. sp.: Mycophagous female: L= 0.76 -0.82 mm, a= 28-36, b= 9.9- 10.9, b’= 5.0-6.3, c= 23.1- 23.4, V= 87.2-89.1, c’= 1.9-2.3, stylet = 8 μm, tail = 32-36 μm. Lateral lines indistinct. Excretory duct cuticularized. Hemizonid just anterior to excretory pore. Spermatheca rounded, bearing large rounded sperms without distinct nuclei. Post vulval uterine sac absent. Tail cylindrical, with an inverted ‘U’-shaped hyaline region; tail terminus broadly rounded to truncated. Mycophagous male: L= 0.54-0.60 mm, a= 29-35, b= 8.7-10.0, b’= 5.1-6.1, c= 21-22, c’= 2.0-2.3, stylet= 7-8 μm, tail= 25- 29 μm, spicules= 16-19 μm. Sperms minute, nucleated. Infective female: L= 0.54-0.68 mm, a= 31.3-42.2, b= 6.8-8.9, b’= 2.4-3.3, c= 18.0- 24.7, V= 84.4-87.7, c’= 1.9-2.7, stylet= 11-14 μm, tail= 22-30 μm. Lip region rounded, raised in the middle. Stylet with prominent, notched knobs. Distal part of uterus with 62-82 μm long, sac-like structure that is devoid of sperms. Post vulval uterine 0.5-1.0 vulval body-width long, without sperms. Tail cylindrical with broadly rounded to truncated terminus. Inner cytoplasm near tip indented as in mycophagous females. Deladenus obtusicaudatus n. sp.: Mycophagous female: L= 0.73 mm, a= 25, b= 7.5-8.6, b’= 3.4-3.9, c= 29.0- 29.3, V= 92.6-93.5, c’= 1.5-1.7, stylet = 9 μm, tail= 25 μm. Excretory duct cuticularized. Hemizonid 19-25 μm behind excretory pore. Spermatheca distinct, sperms rounded without distinct nuclei. Vagina without vulval flap. Post vulval uterine sac absent. Tail cylindrical with broadly rounded to truncated terminus. Mycophagous male: L= 0.49-0.52 mm, a= 24-25, b= 7.0-7.2, c= 26, c’= 1.5- 1.8, stylet= 9 μm, tail= 19-20 μm, spicules= 11-14 μm. Sperms small, nucleated. Infective female: L= 0.59-0.61 mm, a= 26-27, b= 11.1- 11.7, b’= 1.9-2.0, c= 27-29, V= 92.5-92.6, c’= 1.7-1.8, stylet= 17-19 μm, tail= 21-22 μm. Lip region row, flat at upper surface. Lateral lines six. Conus of stylet ventrally curved, basal knobs rounded. Tail short, cylindroid with obtusely rounded terminus. Deladenus oryzae n. sp.: Mycophagous female: L= 0.66-0.96 mm, a= 19-26, b= 7.9, c= 29.1, V= 92.6-93.5, c’= 2.4-2.6, stylet= 7-9 μm, tail= 29-34 μm. Hemizonid adjacent to excretory pore. Spermatheca rounded-oval, sperms rounded without distinct nuclei. Tail conoid, tapering from both sides to a broadly rounded terminus. Mycophagous male: L= 0.53-0.67 mm, a= 25-32, b= 6.1-7.5, c= 16.5-22.4, c’= 2.4-3.4, stylet= 7-9 μm, tail= 27-34 μm, spicules= 16-18 μm. Infective female : L= 0.55-0.64 mm, a=26-30, b= 5.5-6.5 , b’= 1.7-1.9, c= 19.7-22.3, V= 90.8-91.2, c’= 2.9-3.3, stylet= 17-20 μm, tail= 29 μm. Lip region raised at upper surface. Conus of stylet less than 1/3 of stylet length, its dorsal side longer than ventral; shaft with basal swellings. Tail elongated conoid, regularly tapering from both sides to a rounded or digitate terminus. Deladenus zyzyphus n. sp.: Mycophagous female: L= 0.79-1.11 mm, a= 45-51, b= 9.3-11.1, c= 10.7-12.1, V= 85.1-86.3, c’= 6.1-7.0, stylet= 7-9 μm, tail= 69-90 μm. Excretory duct slightly cuticularized. Hemizonid just anterior to excretory pore. Stylet small, with prominent, posteriorly-sloping bifid knobs. Spermatheca indistinct. Vagina without vulval flap. Post uterine sac absent. Tail elongated conoid, regularly tapering from both the sides to a pointed terminus. Mycophagous male: L= 0.49-0.78 mm, a= 30-34, c= 16.2-24.9, c’= 2.4-3.4, stylet = 7-9 μm, tail = 29-34 μm, spicules= 14-15 μm. Sperms minute and nucleated. Infective female: L= 0.87-1.22 mm, a= 49-61, b’= 3.8-5.2, c= 11.2-13.3, V= 85.0-87.2, c’= 6.2-7.5, stylet= 12-13 μm, tail= 75-97 μm. Lip region rounded at upper surface. Conus of stylet nearly 1/3 of stylet length and ventrally curved. Tail elongated conoid, regularly tapering from both sides to a pointed or mucronate terminus. Deladenus cocophilus Nasira et al., 2013 is reported for the first time from India.